Salivary testosterone: a reliable approach to the diagnosis of male hypogonadism - Arregger, Alejandro Luis (2007)
Summary Objetive The purpose of this study was to demonstrate that Sal-T is a reliable biomarker of androgen status in the diagnosis of male hypogonadism. Design In order to validate the salivary testosterone assay (Sal-T), its reproducibility , the agreement with serum free testosterone levels (Free-T) , the correlation with other circulating androgen markers ( bioavailable testosterone , total testosterone) and  cut off values were defined. Patients and Methods We studied 52 eugonadic (E) and 20 hypogonadic (Hy) men. Sal-T was assayed using an adapted radioimmunoassay for serum testosterone. Sal-T concentrations were compared in 9 cases before and after citric acid stimulation of salivary flow-rate.  Free-T and bioavailable testosterone (Bio-T) were calculated by Vermeulen equation  and SHBG were determined by binding assay. Results Sal-T did not depend on  salivary flow-rate and morning samples from 7.00 to 9.00 h were stable. Agreement between Sal-T and Free-T measurements was confirmed in all subjects .  Sal-T levels correlated positively with  all circulating androgens , showing the best correlation with Free-T in E (r=0.92) as well as in Hy (r=0.97).A cutoff value  for Sal-T  £ 0.195 nM  showed 100% of sensibility and specificity to rule out hypogonadism. Conclusions Our data showed  that Sal-T is a reliable marker of testosterone bioavailability. The results support the inclusion of this biomarker as a non invasive approach in the diagnosis of male androgen deficiency.